FACULTY COMPETENCE IN DEVELOPING MULTICULTURAL COMPLETENCIES OF STUDENTS - Nirupama Prakash (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This research seeks to identify multicultural competencies (competence, knowledge and attitudes) unique to teaching and explore their essence and relevance to culturally varied pupils from various countries and ethnic groups. A case study method was used to examine intercultural skills. Qualitative study was based on a feedback survey of students that included open questions. The findings of the study enable the research question to be answered which instructors are essential to intercultural and multicultural competencies. From the viewpoint of the pupils, instructors should be aware that people from various cultural backgrounds have unique requirements. The findings thus have added significant value in identifying the essential multicultural skills of academic instructors and in setting up a framework of learning skills in a global context.